Collective tourism social entrepreneurship: A means for community mobilization and social transformation. (May 2021) - Jørgensen, Matias Thuen; Hansen, Anne Vorre; Sørensen, Flemming; Fuglsang, Lars; Sundbo, Jon; Jensen, Jens Friis
Abstract: Communities depicted by lack of opportunities for development often look to tourism initiatives as a means to combine economic growth and community building. Such activity highlights a nexus between tourism, social entrepreneurship and community development. This nexus has been investigated somewhat in tourism literature, but lacks empirical backing, as well as theoretical refinement. We argue that a collective perspective on social entrepreneurship in the tourism context is needed, and introduce a concept and framework for 'Collective Tourism Social Entrepreneurship'. We investigate how these principles are utilized by local communities to combat depopulation and deterioration in two Danish destinations, and find that the proposed process can create (social) value even if the expected result is never reached. Graphical abstract: Unlabelled Image Highlights: Introduces and defines the concept of Collective Tourism Social Entrepreneurship Challenges the traditional view of the lonely heroic entrepreneur Highlights the need for a more collective perspective on social entrepreneurship Investigates application of CTSE principles to combat depopulation and deterioration Finds that the CTSE process may create (social) value in and of itself.